Elizabeth David And Her Spices, Salt And Aromatics In The English Kitchen: A Reappraisal - Perkins, Blake (Petits Propos Culinaires, 2023)
Regular PPC contributor Blake Perkins offers his re-appraisal of Elizabeth David’s Spices, Salts and Aromatics in the English Kitchen.